A study on some physical and mechanical properties of molded thermal insulation materials produced from perlite and boric acid added forestry by-products. Issue 2 (4th March 2023) - Efe, Fatih Tuncay
ABSTRACT : The tree bark and cones are either burned or left in the forest. In both cases, it causes both environmental problems and a significant loss of economic potential. In this study, some physical and mechanical properties of molded thermal insulation materials produced from natural raw materials were investigated experimentally. In this context, 15 types of sandwich panel materials containing honeycomb-shaped core were produced from pine ( Pinus brutia Ten.) bark and cones. The mean moisture content, density, compressive strength, tensile strength perpendicular to the surface, tensile strength parallel to the surface, and dimensional stability values of the materials were 10.6%, 269.717 kg/m 3, 0.493.06 N/mm 2, 0.011 N/mm 2, 0.150 N/mm 2 and −0.156%, −0.054%, 0.942%, respectively. According to the results, it was determined that the increase in particle size and perlite ratio in the materials produced from the bark decreased the density. Moreover, it was found that the particle size-moisture content relationship and the perlite ratio-moisture content relationship varied in the materials containing bark and cones, that the mechanical properties were higher in the materials containing cones, and that the dimensional stability did not show a regular change.